EMPLOYEE PERFORMANCE IMPROVEMENT OF PT. MALINDO FEEDMILL TBK, GROBOGAN - Juniarti, Emma; Martono, S (Management Analysis Journal, 2019)
Performance is used to measure which targets are used and human resources in achieving company goals. Human resources have a large role for the success of the organization. Therefore, companies are required to develop human resources in order to have reliable skills so that they can win increasingly competitive competition. An employee who has high self-efficacy at work can also be a high resource for employees. The purpose of this study is to analyze the transformation of leadership, work motivation, and self-efficacy on the performance of employees of PT. Malindo Feedmill, Tbk. Grobogan The population in this study were all employees working at PT. Malindo Feedmill, Tbk., Grobogan with proportional random sampling data collection techniques and calculation samples using Slovin formula obtained as many as 158 respondents. Data collection methods using questionnaires, analytical methods using descriptive and multiple linear regression. (1) Transformational leadership has a positive and significant direct effect on employee performance, (2) Work motivation has a positive and significant effect on employee performance, (3) Self-efficacy has a direct and significant effect on employee performance.